Ragam Solusi Ekonomi Islam dalam Mengatasi Masalah Ekonomi - Talitha Destiani Putri; Adria Zahrani Sufni; Rachmad Risqy Kurniawan (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
The purpose of this study is to examine more deeply about the varioussolutions of Islamic economics in overcoming economic problems, especially theeconomic crisis based on the verses of the Qur'an and their interpretations. Thisresearch is library research with the maudhu'i (thematic) interpretation method. Theresults of this study indicate that so far the solution to Indonesia's economic problemshas always relied on only one policy, namely debt, while Islamic economics providesvarious solutions in dealing with economic problems, one of which is the economiccrisis. As in the interpretation of QS. Yusuf verse 67 then in solving economicproblems, Islamic economics does not use only one door or only one solution or oneapproach/method, but comes from various doors, namely using severalapproaches/methods that are solutions to economic problems, especially crises, so thatthe results achieved as expected and avoid failure in an effort to solve economicproblems.